Pengaruh Struktur Modal Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Moderasi pada Perusahaan Energi Sektor Minyak, Gas, dan Batu Bara yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Cut Intan Fadila; Rusnaidi Rusnaidi; Syahrul Maulidi (Politeknik Kampar, 2025)
The purpose of this study is to examine the effect of capital structure on firm value in energy companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023, and to investigate whether profitability moderates the relationship between capital structure and firm value in these companies. This research uses a quantitative method. The population consists of 99 financial report samples from energy sector companies engaged in oil, gas, and coal that are listed on the IDX. The object of this research is energy sector companies in the oil, gas, and coal industries listed on the Indonesia Stock Exchange. The data analysis technique employed is multiple linear regression analysis using EViews software. The type of data used in this study is secondary data. The results of the study show that capital structure has a significant effect on firm value in energy sector companies (oil, gas, and coal) listed on the IDX. Furthermore, profitability moderates the effect of capital structure on firm value in these companies.